Research of Gelatin and Sucrose Augmentation on Physicochemical and Organoleptic Characteristics of Tepache Jelly Candy - Putri, Wulandari Rusadi; Rosida; Rosida, Dedin F. (Asia Pacific Network for Sustainable Agriculture, Food and Energy (SAFE-Network), 2024)
Tepache is a traditional Mexican beverage crafted from pineapple peels, celebrated for its potent antioxidant properties. This research seeks to evaluate the influence of incorporating gelatin and sucrose on the physicochemical and sensory characteristics of jelly candies, while also determining the ideal combination of gelatin and sucrose augmentations that result in a jelly candy preferred by consumers. The experimental design utilized a fully randomized factorial arrangement with two distinct factors. Factor I focused on varying gelatin concentrations of 15%, 25%, and 35%, whereas Factor II involved different stages of sucrose augmentation at 40%, 50%, and 60%. Data analysis was carried out through analysis of variance, followed by the DMRT test in instances of notable variations. The research revealed that the most optimal treatment entailed incorporating 25% gelatin and 60% sucrose, outcoming in jelly candy with a moisture content of 18.55%, ash content of 0.67%, pH of 4.75, vitamin C content of 42.31 mg/100g, the antioxidant activity of 58.55%, omitting sugar content of 13.92%, pattern of 9.25N, and an average liking score, encompassing color (3.36 - neutral), aroma (3.32 - neutral), taste (3.72 - neutral), and pattern (3.76 - neutral).